Metabolic alterations triggered by silicon nutrition is there a signaling role for silicon? - Detmann, Kelly C.; Araújo, Wagner L.; Martins, Samuel C. V.; Fernie, Alisdair R.; DaMatta, Fábio M. (Plant Signal Behav, 2013)
Although the beneficial role of silicon (Si) in stimulating the growth and development of many plants is generally accepted, our knowledge concerning the physiological and molecular mechanisms underlying this response remains far from comprehensive. Considerable effort has been invested in understanding the role of Si on plant disease, which has led to several new and compelling hypotheses; in unstressed plants, however, Si is believed to have no molecular or metabolic effects. Recently, we have demonstrated that Si nutrition can modulate the carbon/nitrogen balance in unstressed rice plants. Our findings point to an important role of Si as a signaling metabolite able to promote amino acid remobilization. In this article we additionally discuss the agronomic significance of these novel observations and suggest Si nutrition as an important target in future attempts to improve yields of agronomic crops.
Keywords: Silicon (Si); Signaling; Metabolite profile; Amino acid remobilization